2006
DOI: 10.1093/pcp/pcl003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Two Flavonoid 3′-Hydroxylase cDNAs Involved in Biosynthesis of Anthocyanin Pigments and 3-Deoxyanthocyanidin Phytoalexins in Sorghum

Abstract: Three unique sorghum flavonoid 3'-hydroxylase (F3'H) cDNAs (SbF3'H1, SbF3'H2 and SbF3'H3) were discovered through bioinformatics analysis. Their encoded proteins showed >60% identity to the Arabidopsis TT7 (F3'H) protein. Overexpression of SbF3'H1 or SbF3'H2 restored the ability of tt7 mutants to produce 3'-hydroxylated flavonoids, establishing their roles as functional F3'H enzymes. In sorghum mesocotyls, SbF3'H1 expression was involved in light-specific anthocyanin accumulation while SbF3'H2 expression was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…In the flavonoid biosynthetic pathway, F3 0 H hydroxylates naringenin or dihydrokaempferol at the 3 0 -position in the B-ring to generate 3 0 ,4 0 -hydroxylated eriodictyol or dihydroquercetin respectively, which are precursors for quercetin (flavonols), procyanidin (flavan-3-ols) and cyanidin-based anthocyanins (Jeong et al, 2006). In addition, the synthesis of some 3 0 -hydroxylated flavonoids involved in pathogen resistance of both monocots and dicots, such as the anti-microbial phytoalexins apigenin, luteolin and luteolinidin in sorghum (Sorghum bicolor) and Soybean (Glycine max), also requires the enzyme activities of F3 0 Hs (Shih et al, 2006;Zabala et al, 2006). In most plants, F3 0 H genes are presented in low copy numbers (Dixon et al, 2002), but they are highly redundant in grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…In the flavonoid biosynthetic pathway, F3 0 H hydroxylates naringenin or dihydrokaempferol at the 3 0 -position in the B-ring to generate 3 0 ,4 0 -hydroxylated eriodictyol or dihydroquercetin respectively, which are precursors for quercetin (flavonols), procyanidin (flavan-3-ols) and cyanidin-based anthocyanins (Jeong et al, 2006). In addition, the synthesis of some 3 0 -hydroxylated flavonoids involved in pathogen resistance of both monocots and dicots, such as the anti-microbial phytoalexins apigenin, luteolin and luteolinidin in sorghum (Sorghum bicolor) and Soybean (Glycine max), also requires the enzyme activities of F3 0 Hs (Shih et al, 2006;Zabala et al, 2006). In most plants, F3 0 H genes are presented in low copy numbers (Dixon et al, 2002), but they are highly redundant in grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…Biotic factors like fungal infection are known to affect flavonoid synthesis in sorghum (Hipskind et al, 1990;Lo and Nicholson, 1998;Nicholson and Hammerschmidt, 1992;Snyder and Nicholson, 1990;Weiergang et al, 1996). Other reports have demonstrated the effect of both genotype and biotic factors on the metabolism of sorghum flavonoids (Boddu et al, 2005;Shih et al, 2006). All of these studies evaluated flavonoids as a collective group, but use of specific compounds is important when they are considered for use as a nutraceutical or colorant.…”
Section: Introductionmentioning
confidence: 99%
“…4), suggesting that antioxidant activity could play a role in chilling tolerance. Wild-type Arabidopsis plants accumulate the flavonols quercetin (3 0 ,4 0 -hydroxylated) and kaempferol (4 0 -hydroxylated), whereas only kaempferol was detected in tt7 mutants, which lack F3 0 H activity (Sheahan and Rechnitz 1992;Schoenbohm et al 2000;Shih et al 2006). Buttery and Buzzell (1973) demonstrated that the T allele is responsible for the formation of quercetin glycosides in leaves; both quercetin and kaempferol glycosides are present in leaves from soybean with tawny pubescence (TT), whereas only kaempferol glycosides are present in leaves from soybean with gray pubescence (tt).…”
Section: Discussionmentioning
confidence: 99%
“…Methanol extracts of flavonoids (see above) were acidhydrolyzed and re-suspended in methanol according to the method of Shih et al (2006). The resultant acid hydrolysates were subjected to high performance liquid chromatography (HPLC) on an HP 1100 HPLC system (Agilent Technologies, CA, USA) equipped with a Pegasil ODS column (inner diameter = 6.0 9 150 mm, Senshu Scientific.…”
Section: Analysis Of Flavonoidsmentioning
confidence: 99%